Electric and energetic properties of small pulse plasma accelerator in expirement - Dosbolayev, M. K.; Kasen, A.; Niazymbetov, A.; Ramazanov, T. S. (Recent Contributions to Physics, 2014)
In this paper shows the results of the electrical properties (current-voltage characteristic “CVC”) of plasma accelerator “ИП-5”. Was investigated the plasma current and the energy density distribution of the plasma flow along the accelerator
Keywords: plasma accelerator; electrical properties; plasma